(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article analyzes the nature of edifying verses. After all, it cannot be denied that moralizing poems, which form the core of the spiritual worldview of the Kyrgyz people, have done an acceptable job of shaping national consciousness, worldview, education and didactics. It must be emphasized that the purpose of edifying poems is to help the younger generation distinguish between black and white, distinguish between good and evil, great and small, respect and honor, life and death, choose the right path, and shape the spiritual vision of the future generation. Also, the object of study of this article is the content, versatility and thematic versatility of edifying poems.